2020
DOI: 10.3233/atde200164
|View full text |Cite
|
Sign up to set email alerts
|

How an OEM Can Become Circular with Remanufacturing: The Case of Robotic Lawn Mowers

Abstract: The consumption of resources is at an alarmingly high level, and there is a high need for resource-efficient alternatives to manufacturing. Remanufacturing is one way to reduce the use of both materials and energy, while still providing products with a like-new condition. This paper aims to define critical areas to assess when applying remanufacturing to original equipment manufacturers (OEMs). The research was conducted by interweaving remanufacturing’s role in a circular economy (CE) with a single case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The case company gained an interest in remanufacturing as part of making contributions towards its sustainability vision. The three Phase 1 studies, shown in Figure 1, concluded that remanufacturing was viable at the case company considering the design of the targeted products, customer perception, and expected return on investment (Kurilova‐Palisaitiene et al, 2020). These positive results enabled a prolongation of the remanufacturing project as the upper management had sufficient material indicating further positive outcomes.…”
Section: The Remanufacturing Initiation At the Case Companymentioning
confidence: 99%
See 2 more Smart Citations
“…The case company gained an interest in remanufacturing as part of making contributions towards its sustainability vision. The three Phase 1 studies, shown in Figure 1, concluded that remanufacturing was viable at the case company considering the design of the targeted products, customer perception, and expected return on investment (Kurilova‐Palisaitiene et al, 2020). These positive results enabled a prolongation of the remanufacturing project as the upper management had sufficient material indicating further positive outcomes.…”
Section: The Remanufacturing Initiation At the Case Companymentioning
confidence: 99%
“…With a basis in the insights from the six studies with various research methods and the decision‐making procedure studied at the case company (Kurilova‐Palisaitiene et al, 2020), a remanufacturing initiation framework was developed: One to guide OEMs in framing the steps to systematically initiate remanufacturing.…”
Section: The 5afirmentioning
confidence: 99%
See 1 more Smart Citation